Successful treatment of pulmonary hypertension due to HIV infection and amphetamine snorting: a case report - Sun, Cuiming; Wen, Ying; Chen, Yanli (Frontiers in Medicine, 2025)
HIV infection is one of the high-risk factors for pulmonary hypertension (PH). HIV-related PH is associated with non-AIDS-related comorbidities. In this study, we report a case of pulmonary hypertension with several concomitant risk factors who experienced a complete clinical improvement after drug rehabilitation, application of anti-retroviral therapy (ART), and sildenafil. A 37-year-old HIV-positive man complained about worsening dyspnea was diagnosed with severe PH. PH in this case was characterized by association with multi-factors, including amphetamine inhalation, HIV infection, bacterial liver abscess, history of splenectomy, and past ventricular septal defect, which was different from previously reported HIV-related PH cases who were associated solely with HIV infection. Our case intends to raise awareness that PH should be suspected among HIV-positive patients with unexplained dyspnea. It is notable that investigating the coexistent risk factors and a multidisciplinary team are crucial for early diagnosis and better prognosis of HIV-related PH.